Human osteoblasts obtained from distinct periarticular sites demonstrate differences in biological function in vitro. Issue 9 (1st September 2021) - Ali, Erden; Birch, Mark; Hopper, Niina; Rushton, Neil; McCaskie, Andrew W.; Brooks, Roger A.
Abstract : Aims: Accumulated evidence indicates that local cell origins may ingrain differences in the phenotypic activity of human osteoblasts. We hypothesized that these differences may also exist in osteoblasts harvested from the same bone type at periarticular sites, including those adjacent to the fixation sites for total joint implant components. Methods: Human osteoblasts were obtained from the acetabulum and femoral neck of seven patients undergoing total hip arthroplasty (THA) and from the femoral and tibial cuts of six patients undergoing total knee arthroplasty (TKA). Osteoblasts were extracted from the usually discarded bone via enzyme digestion, characterized by flow cytometry, and cultured to passage three before measurement of metabolic activity, collagen production, alkaline phosphatase (ALP) expression, and mineralization. Results: Osteoblasts from the acetabulum showed lower proliferation (p = 0.034), cumulative collagen release (p < 0.001), and ALP expression (p = 0.009), and produced less mineral (p = 0.006) than those from the femoral neck. Osteoblasts from the tibia produced significantly less collagen (p = 0.021) and showed lower ALP expression than those from the distal femur. Conclusion: We have demonstrated for the first time an anatomical regional variation in the biological behaviours of osteoblasts on either side of the hip and knee joint. The lower osteoblast proliferation, matrix production, and mineralization from the acetabulum compared to those from the proximal femur may be reflected in differences in bone formation and implant fixation at these sites. Cite this article: Bone Joint Res  2021;10(9):611–618.